1993
DOI: 10.1177/089431849300600210
|View full text |Cite
|
Sign up to set email alerts
|

The Caring Moment and the Green-Thumb Phenomenon among Swedish Nurses

Abstract: People who have a special gift for gardening are sometimes described as having a green thumb. Likewise, some nurses have a green thumb for nursing. The aims of this study were to identify and describe the characteristics of green-thumb nurses and of caring situations. A descriptive-exploratory design was used, and 16 nurses, recruited by their superiors, participated in semi-structured interviews. The findings revealed that the green-thumb nurse is competent, compassionate, and courageous. The essence of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…In the midst of rising public scrutiny, nurse caring is emerging as an important quality indicator (Jensen et al. 1993, 1996, Larrabee & Bolden 2001, Stichler & Weiss 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the midst of rising public scrutiny, nurse caring is emerging as an important quality indicator (Jensen et al. 1993, 1996, Larrabee & Bolden 2001, Stichler & Weiss 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In the midst of rising public scrutiny, nurse caring is emerging as an important quality indicator (Jensen et al 1993, Larrabee & Bolden 2001, Stichler & Weiss 2001. Researchers have found a predictive relationship between nurse caring and both patient advocation and patient satisfaction (Duffy 1992, Wolf et al 1998, Burroughs et al 1999, Dingman et al 1999, Larrabee et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There are times that caring means being hard and doing what others do not want, as was noted in the findings related to responsibility and freedom. Jensen et al (18) described caring as risk-taking, advocacy, fearlessness and connectedness. All of these descriptors can be directly found in the present findings, with the exception of connectedness.…”
Section: Discussionmentioning
confidence: 99%
“…By using competence, compassion, courage and concordance, the nurses caught the patient's wavelength and created caring moments (58). In these caring moments, both patients and nurses realized their intersubjective connectedness and mutual attention and trust.…”
Section: Caring Moments As Connectednessmentioning
confidence: 99%
“…In a study of nurses with a special gift for caring (i.e. excellent in clinical practice), Jensen and Bäck-Pettersson (58,59) found that the ability to intentionally create caring moments was imperative. By analyzing caring situations important to patients, the nurses created caring moments through their consciousness and way of being, using their competence, compassion and courage.…”
Section: The Caring Encountermentioning
confidence: 99%